Working With People With Disabilities: An Interactive Video/Lecture Session for First- and Second-Year Medical Students - Sandra L. Hearn (Association of American Medical Colleges, 2020)
Introduction Negative physician attitudes toward people with disabilities create barriers to health care for these individuals. Barriers can include withholding of standard medical and preventive care, provision of inferior treatment, and patient mistrust of the health care system. Thus, preparing medical students to care for people with disabilities is especially important. Educating health care providers early in their careers can shape their interactions while their approach to patients is still deliberate. Methods We developed an interactive introductory session for first- and second-year medical students on how to approach individuals with observable disability in clinical settings. In the session, we explored—through a combination of lecture, discussion, and patient perspective—how negative physician behavior can create health care barriers, as well as proposed a framework for approaching patients with disability. We presented this session in two formats: (a) a slide deck with instructions that a presenter can use to deliver the session and (b) a stand-alone video introduction with reflective questions. Results The session was evaluated by 151 first-year medical students, with 79% reporting either somewhat or much more comfort approaching individuals with disability following the session. Discussion The integration of patient and physician perspectives, as well as the use of reflective questions, provides the opportunity for students to actively explore reasons for provider discomfort with disability and delineate clinical setting strategies to approach patients with disability.